Optimal root pruning to promote growth and water use efficiency of rice seedlings - ZHU Mei; HU Chenfan; LIU Shuoshuo; LIN Shimiao; LIU Jingzhe (Guanʻgai paishui xuebao, 2025)
【Background and Objective】Improving water use efficiency in agriculture is a critical to alleviating global water stress. As agriculture consumes approximately 62% of global water, optimizing agricultural water use is essential for sustainable resource management. In the soil-plant-atmosphere continuum (SPAC), water transport in soil-root system is a key water cycle component and has attracted increasing research attention. Recent studies have shown that rational an approximate root pruning can improve plant water use efficiency, offering promising strategies for water-efficient agriculture. However, study on root pruning in rice remains limited, with most studies focusing on either timing or intensity, while ignoring their combined effects. This study aims to address this gap.【Method】A field experiment was conducted using two rice varieties, Jingzhan 1 and Luhan 639. Root pruning was performed on the 7 th, 9 th, and 11 th day after germination by cutting the root at 1.5 cm from the root tip, removing half of